2007
DOI: 10.1016/j.rmed.2006.10.010
|View full text |Cite
|
Sign up to set email alerts
|

IL-12-induced T-bet expression and IFNγ release in lymphocytes from asthmatics—Role of MAPkinases ERK-1/-2, p38MAPK and effect of dexamethasone

Abstract: The transcription factor T-box-expressed-in-T-cells (T-bet) is required for T(H)1 lymphocyte differentiation, regulates the IL-12-induced expression of the T(H)1-specific cytokine IFNgamma and may be dysregulated in asthmatics. The modulatory role of extracellular signal-regulated kinase (ERK)-1/-2, p38mitogen-activated protein kinase (MAPK) and dexamethasone on IL-12 induced T-bet and IFNgamma expression was assessed in peripheral blood lymphocytes of 10 atopic asthmatics and 10 nonatopic normals. IFNgamma pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Although the precise mechanism by which p38 MAPK regulates IFN-γ production in CD4 + T cells remains unclear, recent studies have suggested that the activation of the this MAPK pathway is required for T-bet expression (32,33), and T-bet regulates IFN-γ production (34). We therefore examined T-bet expression by Western blot analysis during activation of WT and H1RKO CD4 + T cells.…”
Section: Figurementioning
confidence: 99%
“…Although the precise mechanism by which p38 MAPK regulates IFN-γ production in CD4 + T cells remains unclear, recent studies have suggested that the activation of the this MAPK pathway is required for T-bet expression (32,33), and T-bet regulates IFN-γ production (34). We therefore examined T-bet expression by Western blot analysis during activation of WT and H1RKO CD4 + T cells.…”
Section: Figurementioning
confidence: 99%
“…The role of transcription factors in immune cells has revealed a number of important pathways that initiate or maintain inflammation (1,3,11,12,16,24). Here we show that these two resident structural cells, airway epithelial and smooth muscle, also undergo changes in expression of transcription factors in an inflammatory environment.…”
Section: Discussionmentioning
confidence: 60%
“…In asthma, two stromal cell types play significant roles in the syndrome: the airway epithelial cell and the airway smooth muscle cell (5, 9). Although some information is known about the regulation and action of selected transcription factors of immune cells of the lung and peripheral circulation (1,11,12,24), there is a paucity of data on the expression of transcription factors in airway epithelial and smooth muscle cells. Furthermore, there are no studies that examine a large complement of transcription factors expressed in these cells and their modulation by inflammatory stimuli or ␤-agonists, the most common treatment for asthma.…”
mentioning
confidence: 99%
“…PBMCs were isolated from the peripheral blood of donors as described in Koch et al [33]: Peripheral venous blood obtained by venipuncture was added to anticoagulant-citrate-dextrose solution (ACD: 277 mM D-(+)-glucose; trisbase sodium citrate) as anticoagulant at a final concentration of 10% (v/v). HAES (6-hydroxyethyl starch) was added in a 1:4 ratio.…”
Section: Isolation Of Human Peripheral Blood Mononuclear Cells (Pbmcs)mentioning
confidence: 99%
“…For Ficoll gradient sedimentation cells in HBSS were layered over a Ficoll-paque and centrifuged for 30 minutes at 360 g at 18°C. PBMCs in the upper phase were washed three times with HBSS and resuspended in RPMI 1640 culture medium (Sigma, Munich Germany) containing 10% heat-inactivated FCS (fetal calf serum), 2 mM L-glutamine, 100 U/ml penicillin and 100 μg/ml streptomycin as previously described [18,33]. PBMCs were cultured in RPMI 1640 medium or subjected to immunomagnetic depletion Kits in order to purify monocytes or T cells (see below).…”
Section: Isolation Of Human Peripheral Blood Mononuclear Cells (Pbmcs)mentioning
confidence: 99%